Antinemic activity of ferrocenyl chalcones against Meloidogyne incognita infestation in tomato - YADAV, DINESH K; TRIPATHI, KAILASH PATI; PANKAJ, PANKAJ; KAUSHIK, PRASHANT; RANA, VIRENDRA S; KHATRI, DILIP; SHAKIL, NAJAM A (The Indian Journal of Agricultural Sciences, 2021)
A series of ferrocenyl chalcones using acetylferrocene with different aldehydes were synthesized and their in vitro evaluation against Meloidogyne incognita was reported. The present study was carried out in net house conditions, Division of Nematology, ICAR-IARI, during rabi 2018-19, the bioefficacy evaluation of most effective compounds, identified by in vitro results, along with Carbofuran 3G in pot cultured tomato is reported. The identified, five most effective compounds, (2E)-1-Ferrocenyl-3-(4-bromophenyl)-prop-2-en-1-one (3b), (2E)-1-Ferrocenyl-3-(4- methoxyphenyl)-prop-2-en-1-one (3f), (2E)-1-Ferrocenyl-3-(3,4,5-trimethoxyphenyl)-prop-2-en-1-one (3h), (2E)-1- Ferrocenyl-3-(4-nitrophenyl) prop-2-en-1-one (3m) and (2E)-1-Ferrocenyl-3-(2,6-dichlorophenyl)-prop-2-en-1-one (3o) were undertaken for pot experiment at different concentrations, viz. 20, 40 and 80 ppm and by soil drenching and root dipping methods. The study revealed that all plant growth parameters were positively influenced by these compounds. It was also observed that the presence of electron releasing group positively influences the efficacy and the activity was highest in compound 3f and 3h @ 80 ppm at 30 DAI and 60 DAI. The activity was higher in soil drenching compared to root dipping method.